Синтез и применение нанолистовых структур AlOOH-Fe - Лаптева, Наталья Сергеевна химик (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
In the present study, AlOOH-Fe structures were obtained by water oxidation under mild conditions using Al-Fe bimetallic nanopowder as a precursor. AlFe nanopowder was obtained by electric explosion of two twisted wires in an argon atmosphere. Bimetallic AlFe nanoparticles were chemically active and interacted with water at 60°C. The possibility of nanostructure application for the As(V) removal was shown. The nanostructures adsorb more than 200 mg/g As(V) from aqueous solution. The adsorption kinetics corresponds to the pseudo-second order, and the isotherm is described by the Freundlich equation. The use of non-toxic nanostructures opens up new possibilities for water treatment.